Assessing the Implications of Agricultural Development from the Perspective of Sustainable Livelihoods: Dryland Farming Community in Singosari, Lampung - Ariyanto, Komang (Masyarakat: Jurnal Sosiologi, 2023)
The agricultural sector plays a vital role in rural communities in Indonesia. Agricultural development stands as one of the most crucial development agendas pursued by both governmental and non-governmental entities. An essential aspect to examine within agricultural development is its implications for the livelihoods of farming communities. This study analyzes the implications of agricultural development programs on farmers' livelihoods through the lens of sustainable livelihoods. Employing a qualitative method with a case study approach, the research was conducted among dryland farmers practicing intercropping farming systems. The case study was carried out in Singosari Village, Talang Padang Sub-District, Tanggamus District. Primary data collection involved interviews, participatory observations, documentation, and secondary data through a literature review over a 9-month period. Findings indicate that the implications of agricultural development programs by both state and private actors are unevenly distributed among farmer groups. Cultivation patterns of commodity crops (coffee and cocoa) intervened by agricultural development programs tend to be unsustainable, while non-intervened cultivation remains sustainable. Based on the findings, the researcher recommends that agricultural development interventions consider specific farming practices and local agrarian structures in projecting program implications and benefit distribution. Keywords: Agricultural Development, Sustainable Livelihoods, Dryland Agriculture.